Image analysis reveals environmental influences on the seagrass-epiphyte dynamic relationship for Thalassia testudinum in the northwestern Gulf of Mexico - Huang, Chi; Piñón, Carissa; Mehrubeoglu, Mehrube; Cammarata, Kirk (Frontiers in Marine Science, 2023)
Spatiotemporal patterns in seagrass-epiphyte dynamics for Thalassia testudinum in the northwestern Gulf of Mexico were evaluated through biomass measurements and scanned-image based metrics to investigate the potentially harmful impact of excessive epiphyte accumulations on seagrass condition. Image analysis with Spectral Angle Mapper algorithms distinguished epiphyte and uncovered seagrass leaf pixels to generate a normalized metric of leaf area coverage (epiphyte pixels/total leaf pixels). Imaging metrics were compared to biomass-based metrics seasonally, among three locations with different environmental conditions (depth, salinity, temperature and nutrient levels inferred from sediment porewater measurements) near Redfish Bay, Texas, USA. Image analysis, in conjunction with biomass measures, provides enhanced insight into the seagrass-epiphyte dynamic relationship and how it varies with environmental conditions. Compared with the biomass and morphological measures, image analysis may be more informative as an indicator of environmental changes. Variation in linear regressions of epiphyte biomass vs. epiphyte area (pixels) suggested changes in the thickness and/or density of accumulated epiphytes across environmental contexts and seasons. Two different epiphyte colonization patterns were presented based on the correlation between the normalized metrics of epiphyte load and epiphyte leaf coverage. The epiphyte load was highest at low temperatures and locations with elevated DIN:P ratio in sediment porewater. Conversely, the mean leaf coverage by epiphytes stayed relatively constant (± 10%) across seasons but differed by location (25% ~55% in this case), suggesting that leaf growth in this study is regulated to maintain the proportion of uncolonized leaf surface and that epiphyte coverage plays a role in its regulation.